Characterisation of surface texture using AFM with trimmed probe tip - Ali, Mohammad Yeakub; Lim, BengHai (Maney Publishing, 2006)
This paper discusses the scanning performance of a trimmed atomic force microscope (AFM) tip. A standard tip was trimmed by focused ion beam (FIB) sputtering to achieve a higher aspect ratio and sharpness. Microfeatures produced by FIB sputtering on a single crystal silicon substrate were scanned by AFM tapping mode using both untrimmed and trimmed probe tip. A comparison of the scanning results with analytical calculation showed that the trimmed tips were superior in imaging the profile for both the hole shaped and pin shaped microfeatures. But when using the trimmed high aspect ratio tip, the scanning speed was significantly low. Higher scanning speed usually resulted to tip breakage. The trimmed tips were expensive and justified for special applications.